Natural products against resistant bacterial infections: A systematic literature review - Harshit Kaushik; Ruchika Sharma; Anoop Kumar (The Microbe)
Background: Antibiotic resistance is a global threat and recently, World Health Organization (WHO) has declared antimicrobial resistance as one of the top 10 global public health threats. The existing antibiotics are becoming ineffective which results in serious complications and even death of the patients. Natural products have tremendous potential against resistant infections due to their multimodal mechanism of action. However, the exact potential is unclear so far. Aim: Thus, we have conducted a systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to determine the role of natural products. Methodology: The relevant studies were searched in PubMed and clinical trial websites till 18th February 2022. Results: Out of 11,869 studies, 361 studies were selected for qualitative analysis as per the defined inclusion and exclusion criteria. The results have indicated the antibacterial potential of natural products in concentration/dose/dosage manner under in-vitro, in-vivo, and clinical conditions via different mechanisms of action Conclusion: Overall, available evidence has indicated the potential of natural products against various types of resistant bacterial strains under in-vitro, in-vivo, and clinical conditions.